La coprésence sociale : un objet émergent en communication des organisations - Gino Gramaccia (Communiquer)
The concepts of community, social cohesion, identity, and belonging are the subjects of debate in the current widespread context of job flexibility and insecurity. Relating in these emerging social contexts has taken paradoxical forms from the negotiation of autonomy and community to teleworking and soft forms of cohabitation. Flexible individuals, who are living in unstable situations recreate a social network that suits their professional and personal expectations, by employing the currently available technological, legal, and community tools. This trend, clearly observable in unstable communities, is known as social copresence. This phenomenon opens up a new avenue for research in organizational communication, rapidly unmasking the political undercurrents in what is, finally, known as apolitical pragmatism. In other words, beyond social copresence, employability seems to be conditioned by the implicitly political promotion of a social consensus on job flexibility-insecurity.